Long-Term Effects of Multimodal Treatment on Psychopathology and Health-Related Quality of Life of Children With Attention Deficit Hyperactivity Disorder - Velõ, Szabina; Keresztény, Ágnes; Ferenczi-Dallos, Gyöngyvér; Balázs, Judit (Frontiers in Psychology, 2019)
Aim: The current study aimed to examine the association between long-term (36 months) multimodal (pharmacological and psychological) treatment and psychopathology and Health-Related Quality of Life (HRQoL) in children with attention deficit/hyperactivity disorder (ADHD) from the perspectives of both the children and parents. Method: The sample consisted of 23 children with ADHD (21 boys, 2 girls, mean age = 13.46, SD = 2.36) and 23 healthy control children (11 boys, 12 girls, mean age = 12.49, SD = 1.75). The Mini International Neuropsychiatric Interview for Children and Adolescents (MINI Kid) was applied to measure psychopathology and both parent and self-rated versions of the Inventory for the Measure of the Quality of Life in Children and Adolescents were used to assess HRQoL at baseline and at the 36 month follow-up visit. The ADHD group took part in multimodal (medical and behavioural) therapy. The healthy control group did not get any intervention. Results: At the baseline, the ADHD group was characterized with higher scores in nine MINI Kid scales and showed lower HRQoL than the control group according to both children and their parents. At the 36 month follow-up visit six scale scores (ADHD, social phobia, oppositional defiance and conduct disorder, major depressive episode, dysthymic disorder) showed statistically significant decreases in the ADHD group, while these scores were constant in the control group. Parent-rated HRQoL was significantly higher in the clinical group at baseline than at the end of the study, but there were no significant changes in the control group. Self-reported changes in HRQoL matched parent-reported changes. Interpretation: Multimodal therapy is associated with decreased psychopathology and improved HRQoL over the long term.